2017
DOI: 10.1016/j.jecp.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind in emerging reading comprehension: A longitudinal study of early indirect and direct effects

Abstract: The relation between children's theory of mind (ToM) and emerging reading comprehension was investigated in a longitudinal study over 2.5years. A total of 80 children were tested for ToM, decoding, language skills, and executive function (EF) at Time 1 (mean age=3;10 [years;months]). At Time 2 (mean age=6;03), children's word reading efficiency, language skills, and reading comprehension were measured. Mediation analysis showed that ToM at Time 1, when children were around 4years old, indirectly predicted Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 57 publications
3
34
0
7
Order By: Relevance
“…However, previous studies investigating the link between ToM and reading comprehension have shown mixed results. Whereas some have reported significant direct effects of ToM on reading comprehension, even after accounting for language skills and listening comprehension (Atkinson et al, 2017;Boerma et al, 2017), others have not found direct links after considering language skills or listening comprehension (Guajardo and Cartwright, 2016;Kim, 2017;Ebert, 2020) or they have found no correlations at all (Lockl et al, 2017). However, there is evidence that suggests that, particularly beyond the preschool years, when more advanced measures of reading and more advanced measures of ToM such as higher-order mental reasoning or the reference to mental states in more complex situations are assessed, ToM is related to reading comprehension (Boerma et al, 2017;Florit et al, 2020).…”
Section: Theory Of Mind (Tom)mentioning
confidence: 92%
See 1 more Smart Citation
“…However, previous studies investigating the link between ToM and reading comprehension have shown mixed results. Whereas some have reported significant direct effects of ToM on reading comprehension, even after accounting for language skills and listening comprehension (Atkinson et al, 2017;Boerma et al, 2017), others have not found direct links after considering language skills or listening comprehension (Guajardo and Cartwright, 2016;Kim, 2017;Ebert, 2020) or they have found no correlations at all (Lockl et al, 2017). However, there is evidence that suggests that, particularly beyond the preschool years, when more advanced measures of reading and more advanced measures of ToM such as higher-order mental reasoning or the reference to mental states in more complex situations are assessed, ToM is related to reading comprehension (Boerma et al, 2017;Florit et al, 2020).…”
Section: Theory Of Mind (Tom)mentioning
confidence: 92%
“…Moreover, language is closely connected to children's developing understanding and knowledge about mental states and processes (Astington and Baird, 2005a;Ebert, 2015). Again, particularly in recent years, children's developing understanding of mental states and processes, for example, theory of mind (ToM) and metacognition, have also been discussed as relevant for children's reading comprehension (e.g., Lecce et al, 2010;Neuenhaus et al, 2011;Atkinson et al, 2017;Ebert, 2020). Against this background, the main aim of the present study was to investigate how children's early language competencies -along with their developing knowledge and understanding of mental states and processes -are related to their reading comprehension in early adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…The development of EK in early childhood is tied to the development of theory of mind (Seidenfeld, Johnson, Cavadel, & Izard, 2014), and some work suggests that early EK predicts later theory of mind skills (Blankson et al, 2017; O'Brien et al, 2011). Theory of mind skills underlie children’s metacognitive abilities—including the potential to understand the process of learning—what they know and do not know as well as what their teacher knows (Kuhn, 2000)—and have been linked to both math (Blair & Razza, 2007; Blankson et al, 2017) and reading achievement (Atkinson, Slade, Powell, & Levy, 2017; Blair & Razza, 2007). For example, children who can better understand their own as well as others’ thought processes may more readily grasp what teachers are attempting to teach during math lessons that involve somewhat abstract concepts (Aunola, Leskinen, Lerkkanen, & Nurmi, 2004; Blankson et al, 2017).…”
Section: Ek and Learning: Theoretical Foundationsmentioning
confidence: 99%
“…Recent studies continue to explore ToM "impairment" in both children (for example, Lecheler et al 2020) and adults (for example, Rosenthal et al 2019), frequently positioning these studies within explorations of support for ToM (Holopainen et al 2019;Lecheler et al 2020) or exploring ToM as an element to examine or decode autism presentation (Livingston et al 2019). Reading is a complex task involving the application of knowledge of vocabulary and grammar, together with accessing of prior knowledge, the generation of inference, self-monitoring of understanding and the integration of each of these with information from the text (Kim 2017), with ToM increasingly recognised as an important element to the successful management of this task (Atkinson et al 2017;Dore et al 2018). It may be the case that some autistic readers experience this complexity, and specifically the ToM element of "putting themselves in another's shoes", in an altered way (McIntryre et al, 2017;McIntyre et al 2018).…”
Section: Literaturementioning
confidence: 99%